Key Elements of Failure of the Enterprises Operated by the Women Entrepreneurs - Swetha.M , Jagan Mohan Reddy.M , Sudharani.V, (Indian Journal of Extension Education, 2015)
Women's entrepreneurship is both about women's position in society and about the role of entrepreneurship in the samesociety. Women entrepreneurs faced many obstacles specifically in marketing their products (including familyresponsibilities) that have to be overcome in order to give them access to the same opportunities as men. Empowermentamong women makes them to join in the mainstream of development. Hence the present paper focused on analyzing thekey elements of failure of the enterprises operated by the women entrepreneurs. The elements contributed for the failure ofwomen enterprises are heavy competition, lack of advertisement for the product, lack of remunerative price for theproduct in the market, insufficient working capital and seasonal demand for the product in various enterprises.